Pengaruh Penyampaian Pesan Siaran Perdesaan RRI Kendari terhadap Pengetahuan Petani - Batoa, Hartina; Ma’suf, Assayuthi (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2010)
The research objective was to know the effect of forwarding message of rural broadcast event RRI Kendari in improving farmers’ knowledge. The research executed in November until December 2009 that having a place of sub-district Baruga district Baruga Kendari city. The research executed by taking primary data from responder farmer which amounts to 35, sampling in this research done with simple random sampling method, and secondary data obtained from a related institution or local government. Data obtained, tabulation, percentage and then is analyzed quantitatively with multiple regression analytical method. A result of research indicates that there is an effect of forwarding message of rural broadcast event RRI Kendari in improving farmers’ knowledge in sub-district Baruga district Baruga Kendari city equal to 62,2%. Source and radio media channel RRI is significant elements influences forwarding the message of rural broadcast event RRI Kendari in improving farmers’ knowledge in sub-district Baruga district Baruga Kendari city pertained as knowledge level “Knows that"